Condition of coral cover area in the northern region of Tidung Kecil Island, Thousand Islands - Suhaika, Nada Qitriyyah; Martanto, Renata; Azriel, Muhammad; Nurazizah, Meiza; Salsabilla, Lulu Friska; Fikri, Muhammad; Sriwijaya, Lammargo Muhammad Asyhari; Auliansyah, Dheandra; Firdaus, Erfina Damayanti; Suryanda, Ade (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
This study aims to determine the condition of the coral reef ecosystem on Tidung Kecil Island, Seribu Islands. Observational data collection was carried out in June 2022. The method used in this study was descriptive with the Line Interval Transect (LIT) technique with two repetitions, with the distance between the transect points being 10 meters. 2 repetitions aim to represent the coral cover data on the island's northern part. The data taken are the length and type of coral reef growth, which is then processed to be included in the coral cover area formula. Observational data were then analyzed using the coral cover percentage formula to calculate live coral growth and continued calculating the percentage cover for all categories of live coral lifeforms. Based on the observations, the condition of the coral cover area in the study area is classified as bad, with a percentage of coral cover area of 18.63% and a percentage of non-coral substrate of 48.7%. This is due to the high human activity (such as fishing) and tourism (such as snorkeling).